Etnomedisin dalam Praktik Pengobatan Tradisional Suku Muna di Kelurahan Anggoeya Kecamatan Poasia Kota Kendari - Hasdairta Laniampe; La Niampe; Taufiq Said; Almarsaban Almarsaban; Bainudin Bainudin; Irawati Tapasi; Mursin Mursin (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
Indonesia is recognized as the second most biodiverse country in the world, possessing approximately 28,000 species of flowering plants, around 6,000 of which are classified as traditional medicinal plants. Amid the tide of globalization, traditional medicine continues to play a vital role in Indonesian society, even as modern medicine advances. The use of plants as medicine is deeply intertwined with local traditions, as exemplified by the Muna people, who possess indigenous knowledge in utilizing various medicinal plants. This study aims to identify the types of traditional medicinal plants, methods of preparation, and their use as alternative treatments for broader communities, employing a qualitative descriptive approach. The findings reveal eight types of medicinal plants employed by the Muna people in Anggoeya Village, one of which is guava leaves boiled to treat diarrhea. This research serves as a bridge between the Muna people's local wisdom in traditional healing practices and modern scientific knowledge, supporting the conservation of ethnobotanical knowledge while opening opportunities for the development of natural-based medicines.